THE IMPACT OF ORGANIZATIONAL CHANGE ON JOB SATISFACTION, AND INTENTION TO QUIT: A MEDIATING ROLE OF PSYCHOLOGICAL CONTRACT VIOLATION - Akhtar, Muhammad Naseer; Rong, Long Li (European Scientific Journal, ESJ, 2015)
Organizations today are not in a stable position. The introduction of new advanced technology, increased competition, cost-cutting approach, globalization, have pushed organizations to implement major changes. Change of any type disrupts the existing employment relationships between the employer and employee. This study attempts to examining the relationship between the negative and positive experiences of organizational change (based on mergers and acquisitions, frequent changes, high impact changes, type of changes, history of changes) and job satisfaction, intentions to quit via the mediating role of psychological contract violations. Furthermore, this study reviews papers related to organizational change, and psychological contract with a further view to highlight the importance of psychological contract violations as a consequence of major organizational changes and how employees make sense of these contract violations and organizational changes.